Pleasurable challenges: competing with the ageing body and mind through Ballet for Seniors. Issue 4 (3rd July 2020) - Ali-Haapala, Anja; Moyle, Gene; Kerr, Graham
ABSTRACT: Globally, people's life expectancies are increasing and we are living longer than past generations. In Australia, people aged 65 years and older are expected to represent 22% of the country's total population in 2057. At present, 65 years is the retirement age in Australia and, as a result, it marks the opportunity for many older Australians to start spending more time engaging in leisure activities. This article examines ballet class participation as one such leisure activity. Drawing from a case study of Queensland Ballet's weekly Ballet for Seniors class, this article analyses the focus group discussions of 10 class participants (aged 46 to 82 years), class observations, and teacher interviews. One of the key findings of this case study was that more challenging class content led to a greater sense of satisfaction and pleasure among the class participants. It is proposed that part of the pleasure of dancing ballet as an older adult are the physical and cognitive challenges that are embedded in the structure of ballet.